Influência do hipotireoidismo gestacional experimental na nocicepção e desempenho motor da prole de ratos - Alves, Iura Gonzalez Nogueira (2012)
Thyroid hormones are essential for normal brain development. Therefore thyroid disease may be responsible for the onset of severe neurological disorders. The proper functioning of the maternal thyroid gland, especially during the early stages of pregnancy, plays an important role in ensuring that the offspring have normal brain and body development.We aimed to investigate the impact of experimental gestational hypothyroidism (EGH) on nociceptive threshold and motor activity in the offspring at different postnatal ages (7th, 15th, 23rd, 30th, 60th and 120th postnatal days; PND) in rats. EGH was induced with methimazole (MMI) 0.02% in drinking water from day 9 of gestation until birth. The offspring was assessed for thermal and mechanical nociception using the tail-flick test and vonFrey filaments. Rota-Rod test and grip strength were used to assess motor function. EGH reduced thermal, but not mechanical threshold at all ages studied (p <0.05). Differently, 60 days old females offspring from MMI-treated dams (f-OMTD) were not affected by EGH when tested in the tail-flick. Only males OMTD presented a deficient locomotor performance using the Rota-Rod test (p < 0.01 at 60th PND), and the grip strength meter (p < 0.05 at 120th PND), in comparison to offspring from water-treated dams (OWTD). In conclusion, EGH promotes hypersensitivity to noxious thermal, but not mechanical stimulus, whereas motor performance is reduced and thermal hypernociception remains present, both only in mature males OMTD, suggesting the presence of a protective factor in females.